PopGenReport: simplifying basic population genetic analyses in R. Issue 4 (2nd March 2014) - Adamack, Aaron T.; Gruber, Bernd; Dray, Stephane
Summary Using scripting languages such as R to perform population genetic analyses can improve the reproducibility of research, but using R can be challenging for many researchers due to its steep learning curve. PopGenReport is a new R package that simplifies performing population genetics analyses in R, through the use of a new report‐generating function. The function popgenreport allows users to perform up to 13 pre‐defined and 1 user‐defined analyses through the use of a single command line. Each analysis generates figures and tables that are incorporated into a pdf report and are also made available as individual files (figures are provided in multiple formats, table contents are provided as csv files). The package includes new R functions that simplify the importation of data from a spreadsheet file, examine allele distributions across populations and loci and identify private alleles, determine pairwise individual genetic distances using the methods of Smouse and Peakall (1999) and Kosman and Leonard (2005), respectively, detect the presence of null alleles, calculate allelic richness, and test for spatial autocorrelation in genotypes using the methods of Smouse and Peakall (1999). The package has a modular structure that makes the process of adding new functionality straightforward. To facilitate the addition of user‐designed functions, the package includes a fully customizable module that can be automatically included in the pdf report. To support users not experienced in R, the website (www.popgenreport.org) has a tutorial for the package and a downloadable, portable version of the package with LaTeX pre‐configured for the Windows operating system.